Budesonide/Glycopyrrolate/Formoterol Fumarate Metered Dose Inhaler Improves Exacerbation Outcomes in Patients with COPD without a Recent Exacerbation History: A Subgroup Analysis of KRONOS - Martinez FJ; Ferguson GT; Bourne E; Ballal S; Darken P; Aurivillius M; Dorinsky P; Reisner C (International Journal of COPD, 2021)
Fernando J Martinez,1 Gary T Ferguson,2 Eric Bourne,3 Shaila Ballal,4 Patrick Darken,5 Magnus Aurivillius,6 Paul Dorinsky,3 Colin Reisner4 1Joan and Sanford I. Weill Department of Medicine, Weill Cornell Medicine, New York, NY, USA; 2Pulmonary Research Institute of Southeast Michigan, Farmington Hills, MI, USA; 3AstraZeneca, Durham, NC, USA; 4AstraZeneca, Morristown, NJ, USA; 5AstraZeneca, Wilmington, DE, USA; 6AstraZeneca, Gothenburg, SwedenCorrespondence: Fernando J MartinezJoan and Sanford I. Weill Department of Medicine, Weill Cornell Medicine, New York, NY 10065, USATel +1 646 962 2748Email fjm2003@med.cornell.eduPurpose: In the Phase III, 24-week KRONOS study (NCT02497001), triple therapy with budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler (BGF MDI) reduced exacerbation rates versus glycopyrrolate/formoterol fumarate (GFF) MDI in patients with moderate-to-very severe chronic obstructive pulmonary disease (COPD) and no requirement for a history of exacerbations. We report a post hoc analysis investigating whether the benefits observed were driven by patients with ≥ 1 exacerbation in the 12 months prior to the study.Patients and Methods: Patients received BGF MDI 320/18/9.6 μg, GFF MDI 18/9.6 μg, budesonide/formoterol fumarate (BFF) MDI 320/9.6 μg, or budesonide/formoterol fumarate dry powder inhaler (BUD/FORM DPI) 400/12 μg twice-daily. Post hoc analyses were conducted on exacerbation and lung function results from patients with and without a documented exacerbation in the 12 months prior to the study.Results: Overall, 74% (1411/1896) of the modified-intent-to-treat (mITT) population had no moderate/severe exacerbations in the 12 months prior to the study. BGF MDI reduced exacerbation rates versus GFF MDI in the prior (58%; unadjusted p=0.0003) and no prior (48%; unadjusted p=0.0001) exacerbations subgroups. The magnitude of reduction in exacerbation rates was generally similar within subgroups for BGF MDI versus BFF MDI and BUD/FORM DPI. In the prior exacerbations subgroup, risk during treatment for time to first exacerbation was lower with BGF MDI versus GFF MDI (p=0.0022) and BFF MDI (p=0.0110); excluding the first 30 days of data yielded similar results. The magnitude of reduction in exacerbation rates for BGF MDI compared with GFF MDI increased with eosinophil count.Conclusion: In patients with or without a history of exacerbations in the 12 months prior to the study, BGF MDI reduced exacerbation rates versus GFF MDI, suggesting results observed in the overall population were not driven by the small subgroup with a prior history of exacerbations.Keywords: fixed-dose combination, COPD, exacerbations of COPD